The Role of Financial Literacy in Strengthening the Effect of Digital Platforms and Financial Technology Peer-to-Peer Lending on Capital Access and MSME Growth: An Empirical Study of MSMEs in DKI Jakarta - Zulham Efendi; Lela Nurlaela Wati; Arlis Dewi Kuraesin (Research Synergy Foundation, 2023)
The financial technology sector in Indonesia, particularly in DKI Jakarta, has experienced significant growth due to improvements in the country's technological infrastructure. As of the end of 2022, the Financial Services Authority (OJK), the financial regulator in Indonesia, listed 102 Fintech companies operating in the country. This study employs a quantitative approach using Smart PLS statistics and a sample of 272 respondents to investigate the relationship between digital platforms, financial technology peer-to-peer lending, access to capital, and MSME growth, with a particular focus on the role of financial literacy for MSMEs in five areas of DKI Jakarta. The study's findings demonstrate a positive impact of financial technology, digital platforms, and peer-to-peer lending on MSME productivity, sales, and growth, which are further enhanced by financial literacy.